Development Of Distric Institutions In The Entikong State Border Area, Indonesia - Irfan Setiawan; Udaya Madjid; Sadu Wasistiono (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2022)
Districts on the state border are an important element in state sovereignty, because borders are one of the most important manifestations of territorial sovereignty. Limitations of the tasks and functions of district government institutions at the state border can hinder the development and development of border areas. This study aims to examine the development of district government institutions in the border areas of the country. This study uses a qualitative descriptive method that involves important efforts in data collection, such as conducting interviews with government officials involved with the institutional development of the Entikong district, and Sanggau district officials, the relevant central government, to collect specific data regarding the institutional development of districts on national borders. To analyze the institutional development of the Entikong District government through the concept of Di Maggio and Powell combined with regulations regarding Regional Government. The results of the study revealed that the implementation of district institutions in the Entikong Border Area in governance illustrates the existence of different work norms, tasks and functions, thus requiring different structures and support of resources through the development of districts to become small-town managers. The tasks and functions of the ministries and district government agencies are integrated into the district institutional structure so that they can build and empower district governments and communities on state borders. Keywords: Institutional Development; District; Government; State Borders. Abstrak Wilayah perbatasan negara merupakan unsur penting dalam kedaulatan negara, karena perbatasan merupakan salah satu perwujudan kedaulatan wilayah yang sangat penting. Keterbatasan tugas dan fungsi lembaga pemerintahan Kecamatan di perbatasan negara dapat menghambat pembangunan dan pengembangan kawasan perbatasan. Kajian ini bertujuan untuk mengkaji perkembangan kelembagaan pemerintahan Kecamatan di wilayah perbatasan negara. Penelitian ini menggunakan metode deskriptif kualitatif yang melibatkan upaya penting dalam pengumpulan data, seperti melakukan wawancara dengan pejabat pemerintah yang terlibat dalam pengembangan kelembagaan Kecamatan Entikong, yaitu pejabat kabupaten Sanggau, pemerintah pusat terkait, guna mengumpulkan data spesifik mengenai pengembangan kelembagaan Kecamatan di perbatasan negara. Untuk menganalisis perkembangan kelembagaan pemerintahan Kecamatan Entikong melalui konsep Di Maggio dan Powell dipadukan dengan peraturan tentang Pemerintahan Daerah. Hasil penelitian mengungkapkan bahwa implementasi kelembagaan kecamatan di Kawasan Perbatasan Entikong dalam penyelenggaraan pemerintahan menggambarkan adanya norma kerja, tugas dan fungsi yang berbeda, sehingga membutuhkan struktur dan dukungan sumber daya yang berbeda melalui pengembangan kecamatan untuk menjadi pengelola kota kecil. . Tugas dan fungsi kementerian dan lembaga pemerintah kabupaten diintegrasikan ke dalam struktur kelembagaan Kecamatan sehingga dapat membangun dan memberdayakan pemerintah Kecamatan dan masyarakat di wilayah perbatasan negara. Kata kunci: Pengembangan Kelembagaan; Kecamatan; Pemerintahan; Perbatasan negara.